1989
DOI: 10.1152/jappl.1989.67.6.2579
|View full text |Cite
|
Sign up to set email alerts
|

Aerosol deposition in the lung with asymmetric airways obstruction: in vivo observation

Abstract: Both the total and regional aerosol deposition were measured in six adult sheep before and after an induction of asymmetric airway obstructions, either by local instillation of carbachol solution (CS, 0.1%) distal to the right main bronchus or inhalation challenge of the right lung with carbachol aerosol (CA, 10 breaths). Total lung deposition was determined by monitoring inert monodisperse aerosols [1.0 micron mass median aerodynamic diam (MMAD)] breath-by-breath, at the mouth, by means of a laser aerosol pho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
4
0

Year Published

1994
1994
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 0 publications
2
4
0
Order By: Relevance
“…Therefore the efficacy of drug delivery will be low if the occluded airway is deep in the left lung airways and lead to acute overdose in the localised regions of the right lung airways unnecessarily. Studies published by Kim et al (1983), Kim et al (1989), and Kim (1989) corroborate the simulation findings where the aerosol deposition increased greatly in patients with obstructive airway disease without regard to type of obstructions.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Therefore the efficacy of drug delivery will be low if the occluded airway is deep in the left lung airways and lead to acute overdose in the localised regions of the right lung airways unnecessarily. Studies published by Kim et al (1983), Kim et al (1989), and Kim (1989) corroborate the simulation findings where the aerosol deposition increased greatly in patients with obstructive airway disease without regard to type of obstructions.…”
Section: Discussionsupporting
confidence: 69%
“…The work by Longest, Vinchurkara, and Martonen (2006) however, included double bifurcation models of upper (G3-G5) and central (G7-G9) airways for a four-year-old child where the effects of asthma was modelled as a 30% constriction of the airway branches. Additional studies in obstructed airways (Kim, Brown, Lewars, & Sackner, 1983;Kim, Eldridge, Garcia, & Wanner, 1989;Kim, 1989;Kim & Kang, 1997b), showed that greater deposition occurred in the obstructed lung compared with a normal lung.…”
mentioning
confidence: 97%
“…The observed exaggerated R n response is perhaps best explained by aerosol deposition dynamics. When airways constrict or close, more of a given aerosol deposits in the lung, and the distribution of aerosol deposition is changed such that more aerosol deposits in the central airways (44). Constriction or closure of the distal airways after exposure to methacholine aerosol, as we observed, will therefore have the effect of enhancing methacholine aerosol deposition in central airways, resulting in an exaggerated central airways, or R n , response.…”
Section: Figurementioning
confidence: 67%
“…Numerous studies have shown that in patients with obstructive airway disease, particle deposition patterns within the lung are very heterogeneous, showing marked enhancement of deposition in various local regions (3)(4)(5). Deposition enhancement at local sites has also been demonstrated systematically with various types of simulated airway obstruction imposed in animal models in vivo (6)(7)(8) as well as physical (Received in original form March t t, 1996 and in revised form November 6,1996) Although the researchdescribed in this article has been supported by the United States Environmental Protection Agency, it has not been subjected to Agency review and therefore does not necessarily reflect the views of the Agency, and no official endorsement should be inferred. Mention of trade names or commercial products does not constitute endorsement or recommendation for use.…”
mentioning
confidence: 99%